Selective androgen receptor modulators: comparative excretion study of bicalutamide in bovine urine and faeces - Rojas, Dante Emanuel (2017)
Besides their development for therapeutic purposes, non-steroidal selective androgen receptormodulators (non-steroidal SARMs) are also known to impact growth-associated pathways as ligands of androgenic receptors (AR). They present a potential for abuse in sports and food-producing animals as an interesting alternative to anabolic androgenic steroids (AAS). These compounds are easily available and could therefore be (mis)used in livestock production as growth promoters. To prevent such practices, dedicated analytical strategies should be developed for specific and sensitive detection of these compounds in biological matrices. The present study focused on Bicalutamide, a non-steroidal SARM used in human treatment of non-metastatic prostate cancer because of its anti-androgenic activity exhibiting no anti-anabolic effects. To select the most appropriate matrix to be used for control purposes, different animalmatrices (urine and faeces) have been investigated and SARM metabolism studied to highlight relevant metabolites of such treatments and establish associated detection time windows. The aim of this work was thus to compare the urinary and faecal eliminations of bicalutamide in a calf, and investigate phase I and II metabolites. The results in both matrices showed that bicalutamide was very rapidly and mainly excreted under its free form. The concentration levels were observed as higher in faeces (ppm) than urine (ppb); although both matrices were assessed as suitable for residue control. The metabolites found were consistent with hydroxylation (phase I reaction) combined or not with glucuronidation and sulfation (phase II reactions)